PENGOLAHAN LIMBAH BATANG SAWIT MENJADI PUPUK KOMPOS DENGAN MENGGUNAKAN DEKOMPOSER MIKROORGANISME LOKAL (MOL) BONGGOL PISANG - Nina Veronika, Anna Dhora, dan Sri Wahyuni (Jurnal Teknologi Industri Pertanian, 2019)
One of the main problem in palm plantations during the rejuvenations is the utilization of palm oil waste especially the palm trunks that reaching 220 m3/hectare. Based on that reason, we need a method of utilizing it that can increase the value from palm oil waste, not just for the benefits of oil palm farmers but also for the environment. Palm oil waste has the potential to become the raw material for making organic fertilizer (compost), it has a high nutrient content and can improve the quality of the fertilizer produced. The objective of this research was to produce a bio-fertilizer with a high quality based on the proper standards. This research was conducted in two stages including the produce of  local microorganism (MOL) from banana stem and the composting stage. The composition of local microorganism materials was banana stem: cattle urine: coconut water: brown sugar with the raio of  2: 1: 1: 1. The composting stage was started after all materials were chopped and stirred together before it composted for one month by varying between the main materials and additional ingredients. The compositions of the palm trunks as the main ingredient were divided in five variations, i.e. 3, 6, 9, 12, and 15% (w/w/), this variations were composted together with two types of additional ingredients of POME and goat manure. Based on the results of the compost analysis, the best composition was the variables of palm trunks: pome: rice husk: ash = 3: 10: 2: 1 with the results of analysis were water content of 16.30%, total NPK of 6.08% , c-organic content of 44.10% , the ratio C/N of 16.30 and pH of 8.16 and it had been fitted with bio-fertilizer standard (Permentan No. 70/Permentan/SR. 140/10/2011).Keywords: palm oil replantation, bio fertilizer, palm oil trunks, decomposer, local microorganism